Ethnic Newspapers as Transcultural Spaces: A Case Study of The Korea Daily Chicago - Ha, Jae Sik (Department of Communications, Universitas Islam Indonesia, 2025)
This study examines how The Korea Daily Chicago, a Korean ethnic newspaper with more than 40 years of history in the U.S. Midwest, fulfills its journalistic mission while navigating organizational and economic challenges. Following the closure of its parent company’s Chicago branch in 2018, the newspaper has operated independently, offering a unique case for understanding ethnic media survival strategies amid declining print readership, limited staffing, and the COVID-19 pandemic. Using participant observation of newsroom practices and semi-structured interviews conducted in September 2021, this qualitative case study found that the newspaper maintains transnational partnerships with The Joongang Daily Seoul and The Korea Daily Los Angeles to secure stable news content, while also relying heavily on advertising from Korean-owned businesses to sustain local operations. These practices illustrate how ethnic newspapers serve not only as business enterprises but also as transcultural and glocal spaces. The case of The Korea Daily Chicago sheds light on the precarious yet adaptive role of ethnic newspapers in the U.S., positioning ethnic media as vital cultural institutions.